2009
DOI: 10.1111/j.1365-2842.2009.01998.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function and number of teeth in a community‐dwelling elderly population without dementia

Abstract: Although the number of sound or decayed teeth has been reported to be associated with cognitive function in elderly populations with dementia, little is known about this association in elderly populations without dementia. We evaluated this relationship, with adjustment for confounding factors, in Japanese populations of 60-year-old (n = 270; 120 males and 150 females) and 65-year-old (n = 123; 57 males and 66 females) individuals residing in Fukuoka Prefecture of Japan. Dental examinations were performed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 19 publications
5
28
1
Order By: Relevance
“…Other population studies in Japan, Korea, Italy and America have also demonstrated similar results; increased number of missing or decayed teeth is associated with higher odds of cognitive impairment [37][38][39] When hippocampal-dependent cognitive functions and tooth loss was investigated, it was found to uniquely contribute to a significant variation in episodic and semantic memory performance, but an association between working memory, visuo-spatial ability and processing speed was not found [40]. This is yet another study with results adding to the accumulating evidence that there is a relationship between hippocampal-dependent cognitive functioning and number of teeth, however they state that longitudinal analyses are needed to shed further light on the potential causal relationship [40].…”
Section: Outcome Of Human Studiessupporting
confidence: 52%
See 2 more Smart Citations
“…Other population studies in Japan, Korea, Italy and America have also demonstrated similar results; increased number of missing or decayed teeth is associated with higher odds of cognitive impairment [37][38][39] When hippocampal-dependent cognitive functions and tooth loss was investigated, it was found to uniquely contribute to a significant variation in episodic and semantic memory performance, but an association between working memory, visuo-spatial ability and processing speed was not found [40]. This is yet another study with results adding to the accumulating evidence that there is a relationship between hippocampal-dependent cognitive functioning and number of teeth, however they state that longitudinal analyses are needed to shed further light on the potential causal relationship [40].…”
Section: Outcome Of Human Studiessupporting
confidence: 52%
“…The act of mastication is thought to exert effects on the hippocampus through increasing cerebral blood flow and allowing entry of growth factors in to the DG, or through sensori-motor input affecting the rate of neurogenesis [36]. In humans, it was found that masticatory ability/tooth loss was positively correlated with having greater odds of cognitive impairment, reflecting results depicting the possible causal relationship seen in the animal models [29,[37][38][39]. Investigation into this, such as with longitudinal studies would be helpful in establishing the extent to which mastication impacts on mental health, and whether this is through a mechanism involving AHN.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous epidemiological studies have reported that a strong negative correlation between the number of existing teeth and the risk of developing dementia [27], a finding that may relate to decreased mastication during eating. Based on such reports, dental treatments to maintain teeth as long as possible are considered to be important to preserve higher brain function, however, it is unclear whether improvement in oral health itself or general fitness associated with oral health had the most impact on the brain function.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth loss can result in pain and often lead to reduced quality of life, social isolation, and inadequate nutrition due to problems with chewing and swelling. Oral health diseases are more often seen in people with poorer cognitive ability [2], low education [3], and lower income [4]. These factors may associate to risk behaviors related to health beliefs and lifestyles, including dental care during the life course.…”
mentioning
confidence: 99%